Hubungan antara Pengetahuan dan Pemahaman Siswa tentang Pencemaran Logam Berat dengan Pembentukan Karakter Siswa dalam Menjaga Keberlangsungan Lingkungan Hidup - Sunaryo Sunaryo (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2017)
Abstract This research is about the understanding of junior high school students about heavy metal pollution in air, water, and land. The research was conducted at Labschools Junior High School, Rawamangun, East Jakarta in 2016 with a sample of 125 students taken from proportional random sampling, using correlational survey method. The results of this study obtained three conclusions. There is a positive and significant relationship between: 1) Knowledge of heavy metal contamination in air, water, and land with the character of student in maintaining environmental sustainability with research result correlation coefficient (ry1) equal to 0,643 and its coefficient of determination (r²y1) is 0,413 with regression equation Ŷ = 53,832 + 2.579X1; 2) The students understanding about heavy metal pollution in air, water, and land with the character of students in environmental sustainability with the result correlation coefficient (ry2) of 0.950 and its coefficient of determination (r²y2) is 0.902 with regression equation Ŷ = 9.390 + 0.952X2; 3) Student's knowledge and understanding about heavy metal contamination in air, water, and land together with student character in maintaining environmental sustainability with result correlation coefficient (ry12) equal to 0,950 and its coefficient of determination (r²y12) is 0,903 with regression equation Ŷ = 8,475 + 0.086X1 + 0.938X2. These indicates a change in the character of students in maintaining significant environmental sustainability. Keywords: student character, knowledge, environmental understanding. Abstrak Telah dilakukan penelitian pemahaman siswa SMP tentang pencemaran logam berat di air, udara dan daratan. Penelitian dilaksanakan di Sekolah Menengah Pertama Labschools, Rawamangun, Jakarta Timur pada Tahun 2016 dengan sampel 125 orang siswa yang diambil dari multitage proportional random sampling, dengan menggunakan metode survey korelasional. Hasil penelitian ini mempeoleh tiga kesimpulan. Terdapat hubungan positif dan signifikan antara: 1) Pengetahuan tentang pencemaran logam berat di air, udara, dan daratan dengan karakter siswa dalam menjaga keberlanjutan lingkungan hidup dengan koefisien korelasi (ry1) sebesar 0.643 dan koefisien determinasi (r²y1) sebesar 0,413 dengan persamaan regresi Ŷ=53.832+2.579X1; 2) Pemahaman siswa tentang pecemaran logam berat di air, udara dan daratan dengan karakter siswa dalam keberlanjutan lingkungan hidup dengan koefisien korelasi (ry2) sebesar 0.950 dan koefisien determinasi (r²y2) sebesar 0,902 dengan persamaan regresi Ŷ=9.390+0.952X2; 3) Pengetahuan dan pemahaman siswa tentang pencemaran logam berat di air, udara, dan daratan secara bersama-sama dengan karakter siswa dalam menjaga keberlanjutan lingkungan hidup dengan koefisien korelasi (ry12) sebesar 0.950 dan koefisien determinasi (r²y12) sebesar 0,903 dengan persamaan regresi Ŷ=8,475+0,086X1 + 0,938X2. Hal ini menunjukkan adanya perubahan karakter siswa siswa dalam menjaga keberlanjutan lingkungan cukup signifikan. Kata-kata kunci : karakter siswa, pengetahuan, pemahaman lingkungan.